Faktor-Faktor Yang Mempengaruhi Praktik Earnings Management - Monica, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this empirical research is to obtain empirical evidence about the influence of firm size, leverage, profitability, firm age, and free cash flow on earnings management of companies in the property, real estate, and building construction listed in Indonesia Stock Exchange. The amount period of observation in this research is the year 2015-2017. The method used in sample selection is purposive sampling method. In this research 51 companies in the manufacturing industry are selected as sample. In this research, 51 companies that are selected are analyzed by using Eviews 10.0. The result of this research shows profitability and free cash flow have a significant effect on the earnings management and firm size, leverage, and firm age doesn’t have significant effect on the earnings management